Strategi Integratif dalam Mendorong Pertumbuhan Ekonomi: Pendekatan Data Panel pada Negara-Negara ASEAN - Mely Agustina; Rachel Jessica; Neli Aida; Muhammad Mufti Hudani; Qurrota Ayu Nindien (CV. ITTC INDONESIA, 2025)
The ASEAN region has seen rapid economic openness, yet the benefits for growth remain uneven. Some countries gain from investment inflows and expanded trade, while others struggle with structural limitations. This study aims to examine the influence of trade openness and foreign direct investment (FDI) on economic growth, and to assess their joint effect as an integrative strategy. Using panel data from 11 ASEAN countries between 2014 and 2024, a Random Effect regression model with clustered standard errors is employed. The findings reveal that FDI supports growth, whereas trade openness alone has a negative impact. However, the interaction between FDI and trade openness becomes positively significant under the Fixed Effect model, suggesting a synergistic relationship. Exchange rates are also positively associated with growth, while inflation appears insignificant. These results highlight the need for holistic economic policies. The implication is that ASEAN’s development strategies should integrate openness with investment, supported by domestic readiness, to achieve inclusive and sustainable growth.